2014
DOI: 10.3329/sja.v11i2.18410
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-Priming of Seed Improves the Water Use Efficiency, Grain Yield and Net Economic Return of Wheat under Different Moisture Regimes

Abstract: Wheat is the second most important staple food crop of India and contributes a major share to food basket of the country. Since majority of the area under wheat is irrigated, it consumes huge quantity of fresh water for its cultivation. The availability of good quality water for irrigation is decreasing over a period of time due to vagaries of monsoon, urbanization and industrialization. The biggest challenge on this front is to improve the efficiency and productivity of water being used in existing cropping s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…Results showed that 2% SSP recorded higher seed yield of 1705 kg/ha with significantly higher N uptake. Sharma et al, (2013) conducted an experiment to study the various seed priming methods for seed germination, seedling vigour and fruit yield in okra. Seeds were subjected to four priming methods, namely, hydro-priming, osmopriming, halo-priming and solid matrix along with control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that 2% SSP recorded higher seed yield of 1705 kg/ha with significantly higher N uptake. Sharma et al, (2013) conducted an experiment to study the various seed priming methods for seed germination, seedling vigour and fruit yield in okra. Seeds were subjected to four priming methods, namely, hydro-priming, osmopriming, halo-priming and solid matrix along with control.…”
mentioning
confidence: 99%
“…It is concluded that seed priming may serve as an appropriate treatment for accelerating the emergence of sorghum genotypes studied. Meena et al, (2013) conducted an experiment for two consecutive years 2010-11 and 2011-12 to evaluate the influence of hydro-priming grain yield of wheat. The experiment was conducted with seed priming treatments (dry seed, hydro-priming, and pre-germinated seeds) in subplots.…”
mentioning
confidence: 99%
“…Interaction between treatments and soaking time revealed that hydro priming with 2 hrs priming duration was most effective for enhancing the rate of germination. Meena (2013) found that seed hydropriming resulted in earlier seedling establishment, which contributed to better crop stand, increased tillering and higher grain yield in wheat than dry seed control. On the contrary, seed priming with KNO improved cotton emergence in green house as compared to hydropriming (Ahmadvand ., 2012b).…”
Section: Resultsmentioning
confidence: 99%
“…Hence it can be concluded that primed seeds have suppressive effect on weeds. Halopriming enhanced the competitive ability of wheat crop against weeds (Meena et al, 2013). Effect on water use efficiency: Early and synchronized field emergence observed in seed priming treatments resulted in more leaf area and early canopy development.…”
Section: Physiological and Biochemical Changes During Seed Primingmentioning
confidence: 98%